Vitamin E Facilitates the Inactivation of the Kinase Akt by the Phosphatase PHLPP1 - Huang, Po-Hsien (2013)
Vitamin E is a fat-soluble vitamin that includes isomers of tocopherols and tocotrienols which are known for their antioxidant properties. Tocopherols are the predominant form encountered in the diet and through supplementation, and have garnered interest for their potential cancer therapeutic and chemopreventive effects, which include the dephosphorylation of Akt, a serine/threonine kinase that plays a pivotal role in important cellular processes, such as cell growth, survival, metabolism and motility. Full catalytic activation of Akt requires phosphorylation at both Thr(308) and Ser(473). Dephosphorylation of Ser(473) drastically reduces Akt catalytic activity and the number of downstream substrates it can regulate. The mechanism by which α- and γ-tocopherol facilitate the selective dephosphorylation of the kinase Akt at Ser(473) was investigated. We showed that this site-specific Akt dephosphorylation was mediated through the pleckstrin homology (PH) domain-dependent recruitment to the plasma membrane of Akt and PHLPP1 (PH domain leucine-rich repeat protein phosphatase, isoform 1), a phosphatase that dephosphorylates Akt at Ser(473). The ability of α- and γ-tocopherol to induce PHLPP-mediated Akt inhibition established PHLPP as a “druggable” target. We structurally optimized these tocopherols to obtain derivatives with greater in vitro potency and in vivo tumor-suppressive activity in two prostate xenograft tumor models. Binding affinities for the PH domains of Akt and PHLPP1 were greater than for other PH domain-containing proteins, which may underlie the preferential membrane recruitment of these proteins. Molecular modeling revealed the structural determinants of the interaction with the PH domain of Akt that may inform strategies for continued structural optimization. These findings describe a mechanism by which tocopherols facilitate the dephosphorylation of Akt at Ser(473), thereby providing insights into the mode of antitumor action of tocopherols and a rationale for the translational development of tocopherols into novel PH domain-targeted Akt inhibitors.